UPAYA TERKAIT PENCEGAHAN PENULARAN CORONAVIRUS DISEASE (COVID-19) DAN KEGAWATDARURATAN SELAMA KEHAMILAN PADA IBU HAMIL - Ida Mariana Sihombing (Akper Kesdam I/Bukit Barisan Padang, 2022)
The world is experiencing a health crisis, including the State of Indonesia, which is caused by the Covid-19 Virus which sent Indonesia experiencing a pandemic period like today. Covid-19 virus from all walks of life, gender and all ages, without discriminating between pregnant women who are a vulnerable group to be infected with the Covid-19 virus who require efforts to prevent transmission of the Covid-19 virus. The purpose of the study was to determine the efforts of pregnant women to prevent being infected with Covid-19. The method used is descriptive, the sample used in this study was 46 pregnant women at Pemancungan Health Center. The results showed that the age of pregnant women aged 31 years and over was 18 people (39%). Age 26-30 15 people 32% and age 20-25 years as many as 13 people 29%. Education of pregnant women who have elementary education as many as 3.5% of elementary school, 5 people of junior high school 11%, high school 31 people 67.3% and university as many as 7 people 15.2%. The work of pregnant women found that as housewives were 32 people 69.6%, who became private employees were 12 people 26%, and those who became civil servants were 4.4%. Attitudes of pregnant women were found to have a Positive Attitude of 18 people 39%, and who have a Negative Attitude as many as 28 people 61%. From the data obtained on the Knowledge variable of pregnant women, it was obtained that 17 people had poor knowledge 37%, and those who had good knowledge were 29 people 63%. From the data obtained on the variable of pregnant women's actions, it was found that 27 people who had bad actions were 58.6%, and those who had good actions were 41.4%.